(untitled) (Al-Farooq Journal of Sciences, 2026)
This research explores the possibility of using Spiking Neural Networks (SNNs), one of the modern artificial intelligence technologies, to design simple and interactive environmental simulation programs suitable for school students in Libya The proposed approach aims to support green education and improve environmental awareness in a clearer and more engaging way In many cases, environmental topics in schools are presented mainly through theoretical explanations, which may make some concepts less connected to students’ real-life experiences and practical understanding In addition, there are technical and logistical challenges that limit the use of advanced environmental simulation programs in the Libyan educational environment, especially since many of these systems require powerful devices or continuous high-speed internet access, which may not always be available to all students. The study adopts a descriptive-analytical approach while also benefiting from intelligent system design methods Spiking Neural Networks (SNNs) operate through a brain-inspired mechanism that processes information using discrete spikes, helping reduce energy consumption and improve software efficiency compared to some traditional models These characteristics make it possible to develop environmental simulation applications that can run effectively on ordinary smartphones and commonly available student devices without requiring complex technical infrastructure or high operational costs. The proposed simulations can also present interactive educational scenarios related to the Libyan environment, such as groundwater depletion, vegetation decline in the Green Mountain region, desertification, and the impact of renewable energy use. This allows students to interact with environmental issues in a practical way through experimentation, observation, and exploring the outcomes of different decisions in a simplified digital learning environment. The study suggests that integrating modern artificial intelligence technologies into educational software may help improve learning methods by making students more engaged and active in the learning process, moving beyond memorization toward experience-based and interactive learning It also highlights the importance of designing simple and engaging user interfaces with motivational and interactive elements that support better understanding and improve students’ learning experience.